A case of membranous nephropathy associated with relapsing polychondritis - Ji-eun Lee; Eun Kyoung Lee (The Korean Society of Nephrology, 2012)
Relapsing polychondritis (RP) is a rare, chronic, and potentially fatal multisystemic inflammatory disorder targeting cartilaginous structures. This disorder is frequently associated with rheumatoid arthritis, systemic vasculitis, connective tissue diseases, and hematologic disorders, but renal involvement is unusual. In the literature, associated renal pathology includes mesangial expansion, IgA nephropathy, tubulointerstitial nephritis, and segmental necrotizing crescentic glomerulonephritis. We report a case of a 49-year-old male found to have RP and nephrotic syndrome, with confirmed membranous nephropathy on kidney biopsy. He responded well to corticosteroids and cyclosporine. This is the first case of renal associated RP confirmed by renal biopsy in Korea. Membranous nephropathy associated with RP has never before been reported.